2021
DOI: 10.1186/s12934-021-01519-0
|View full text |Cite
|
Sign up to set email alerts
|

Purification and identification of a surfactin biosurfactant and engine oil degradation by Bacillus velezensis KLP2016

Abstract: Engine oil used in automobiles is a threat to soil and water due to the recalcitrant properties of its hydrocarbons. It pollutes surrounding environment which affects both flora and fauna. Microbes can degrade hydrocarbons containing engine oil and utilize it as a substrate for their growth. Our results demonstrated that cell-free broth of Bacillus velezensis KLP2016 (Gram + ve, endospore forming; Accession number KY214239) recorded an emulsification index (E24%) from 52.3% to 65.7% against different organic s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In previous studies, a lipopeptide showed 68 ± 0.5% emulsification activity (E24) [ 7 ]. A cell-free broth of B. velezensis showed 56.2% E24 with engine oil [ 31 ]. A biosurfactant from mutant A. niger M2 showed 62.30% of E24 with 59.81 cm 2 oil displacement area [ 32 ], and a 66.4 cm 2 oil displacement area was shown by a biosurfactant from R. arrhizus [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, a lipopeptide showed 68 ± 0.5% emulsification activity (E24) [ 7 ]. A cell-free broth of B. velezensis showed 56.2% E24 with engine oil [ 31 ]. A biosurfactant from mutant A. niger M2 showed 62.30% of E24 with 59.81 cm 2 oil displacement area [ 32 ], and a 66.4 cm 2 oil displacement area was shown by a biosurfactant from R. arrhizus [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lipopeptides are the type of natural product produced by non-ribosomal peptide synthases (NRPS) ( De Giani et al, 2021 ), which are huge multifunctional enzyme clusters ( Williams and Trindade, 2017 ; Lamilla et al, 2021 ). Surfactin is considered one of the most potent biosurfactants ( Meena et al, 2021 ) composed of cyclic lipopeptides with seven amino acid ringed structures linked to a fatty acid chain through lactone linkage ( Figure 3 ; Onaizi, 2018 ; Sarwar et al, 2018 ). Table 1 summarizes the type of biosurfactant as well as the microbes that produce them and their roles in pesticide remediation.…”
Section: Biosurfactants: the Next Age Compounds In Pesticide Remediation And Their Typesmentioning
confidence: 99%
“…In size exclusion chromatography, several column volumes of sodium phosphate buffer (20 mM) were used to wash out the Sephadex G-25 packed matrix (pH 7.5). The DEAE active fraction with biosurfactant was put onto the surface of a Sephadex column(G-25) and eluted with 20 mM sodium phosphate buffer (pH 7.5), with fractions collected based on the molecular weight (Meena et al 2021). HPLC is developed to perform the qualitative and quantitative analysis of the biosurfactant like rhamnolipids and lipopeptides.…”
Section: Chromatographymentioning
confidence: 99%
“…HPLC is developed to perform the qualitative and quantitative analysis of the biosurfactant like rhamnolipids and lipopeptides. Qualification and characterization of the biosurfactant can be executed by this method (Meena et al 2021).…”
Section: Chromatographymentioning
confidence: 99%
See 1 more Smart Citation